Neolignans from Virola carinata - Gottlieb, Otto Richard (Phytochemistry, 2020)
The wood of Virola carinata (Benth.) Warb. contains besides the known neolignans (+)-guaiacin and (-)-galcatin, (-)-isootobaphenol [(2R,3S,4S)-4-guaiacyl-2,3-dimethyl-6,7-methylenedioxytetralin], in addition to 7,4′-dimethoxyflavanone. © 1976.